2018
DOI: 10.1186/s12913-018-3503-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between migrants’ purchasing of commercial medical insurance and urbanisation in China

Abstract: BackgroundOver the past 40 years, the Chinese government has diligently promoted the market-oriented reform of the health insurance system. However, as it is affected by the urban-rural dual structure, most rural-to-urban migrants are excluded from local public health services and medical insurance schemes in the cities in which they live. Buying local commercial medical insurance (CMI) is an important way for migrants to obtain local medical services. Therefore, this study’s purposes were to explore the city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
0
14
0
6
Order By: Relevance
“…Patients living in rural areas, who usually had a relatively low economic status and were insured by NCMS,25 were ostensibly at a greater risk of CHE. This was the result of the ‘urban–rural dual structure’ of the medical insurance system in China,26 which showed a significant difference in coverage reimbursement scope, payment level and funding level 27. Besides, our study found that a higher severity level of VI caused higher direct costs but received a lower reimbursement rate, which resulted in a dramatically increased risk of CHE with the severity of VI.…”
Section: Discussionmentioning
confidence: 64%
“…Patients living in rural areas, who usually had a relatively low economic status and were insured by NCMS,25 were ostensibly at a greater risk of CHE. This was the result of the ‘urban–rural dual structure’ of the medical insurance system in China,26 which showed a significant difference in coverage reimbursement scope, payment level and funding level 27. Besides, our study found that a higher severity level of VI caused higher direct costs but received a lower reimbursement rate, which resulted in a dramatically increased risk of CHE with the severity of VI.…”
Section: Discussionmentioning
confidence: 64%
“…Third, this study found that registered permanent residence status is the most important socioeconomic factor affecting SRH. Under the background of the urban-rural dual structure in China [ 49 ], registered permanent residence reflects the socioeconomic status of residents. Registered permanent residence status has been widely accepted as a factor associated with many diseases [ 50 ], which obviously affects SRH [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physically demanding job and poor work environment may induce migrants’ chronic diseases and physical injuries, which subsequently increase the risk of mental illness. Furthermore, due to the limited access to health care and the poor flexibility of medical insurance transferability, migrants may have to bear more burden of medical expenses without reimbursement, which can also contribute to their life pressure and emotional problems [ 20 , 21 , 22 ]. In addition, with the lack of social pension insurance, migrants might also develop negative emotions, such as anxiety and depression, when considering their living quality after they become old [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%